Keputusan Pembelian Produk Wardah Ditinjau Dari Promosi, Citra Merek Dan Kualitas - Rima Ayu Wulandari; Eny Kustiyah; Sri Hartono (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to determine and analyze the effect of promotion, brand image, and quality. This research is expected to provide an overview for all consumers in making purchasing decisions on Wardah products. The sampling method used was purposive sampling method. Respondents who were sampled in this study were 55 employees. The results of the hypothesis analysis show that the promotion variable (H1), brand image (H2), and quality (H3) have an effect purchasing decisions. Keywords: Promotion, Brand Image, Quality, and Purchase Decisions